2000
DOI: 10.1007/pl00008189
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of four embryo-specific mutants in Zea mays reveals that incomplete radial organization of the proembryo interferes with subsequent development

Abstract: Using confocal laser scanning microscopy we have characterized early and intermediate stages of maize wild-type embryogenesis and compared to mutant development of four different embryo-specific mutations, emb *-8518, emb*-8521, emb*-8537, and emb*-8542. Confocal laser scanning microscopy is well suited to study embryo development in maize in a nondisruptive manner from shortly after fertilization to late stages in embryogenesis. The analysis of the mutant morphology indicated that two of the recessive mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 29 publications
3
6
0
Order By: Relevance
“…As soon as polar localization of ZmPIN1 was observed in the apical anticlinal membranes of the embryo proper outer cell layer, differentiation of the protoderm started. It has been reported that the protoderm is the first evidence of differentiation in maize embryo (Elster et al, 2000), and we observed that this differentiation is correlated with high auxin accumulation.…”
Section: A Model For Zmpin1-mediated Auxin Transport During Embryogensupporting
confidence: 67%
See 1 more Smart Citation
“…As soon as polar localization of ZmPIN1 was observed in the apical anticlinal membranes of the embryo proper outer cell layer, differentiation of the protoderm started. It has been reported that the protoderm is the first evidence of differentiation in maize embryo (Elster et al, 2000), and we observed that this differentiation is correlated with high auxin accumulation.…”
Section: A Model For Zmpin1-mediated Auxin Transport During Embryogensupporting
confidence: 67%
“…At the end of the proembryo stage, the protoderm specifies as a single layer of homogenously sized peripheral cells surrounding the embryo proper. Maize mutants impaired in the restriction of embryonic protoderm-specific genes have been shown to fail in establishing a normal radial organization and to enter the morphological phase of embryogenesis (Elster et al, 2000). Embryonic differentiation continues with the adaxial/abaxial regionalization that is marked by the expression of ZmDRN (Zimmermann and Werr, 2005), a potential ortholog of the Arabidopsis DORNRÖ SCHEN (DRN), on the abaxial side, followed by lateral initiation of the shoot apical meristem (SAM) at the adaxial surface.…”
mentioning
confidence: 99%
“…Still others suggest that the scutellum and coleoptile together comprise the apical and basal components of the single grass cotyledon, in which the scutellum represents the highly modified upper leaf component and the coleoptile represents the sheathing base of the cotyledon. Interesting maize mutants exist that lack a coleoptile, but show normal development of embryonic leaves (Elster et al, 2000). In addition, expression of the ltp2 (lipid transfer protein 2) gene is found in the outer cell layer of the scutellum and coleoptile, but is excluded from the L1 layer of the SAM and the epidermis of true leaf primordia (Sossountzov et al, 1991;Bommert and Werr, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The drastic effects observed on embryo development using our transgenic approach is reminiscent of what has been described in two embryo-specific (emb) mutants emb*-8518 and emb*-8521 in maize (Elster et al, 2000). Unlike wild-type development, the expression of ZmOCL1, a cognate gene of PaHB1, is retained in the inner cells of the two mutant embryos.…”
Section: Pahb1 Has An Evolutionary Conserved Outer Cell Layer-specifimentioning
confidence: 61%